Deciphering ligand-controlled charge transfer from a metal-organic framework to cadmium sulfide for enhanced photocatalytic hydrogen evolution reaction - Singh A.K.; Jaryal A.; Patel S.K.; Kumar D.; Subramaniam Iyer E.S.; Kailasam K.; Indra A. (My University, 2025)
The suitable choice of a cocatalyst plays an important role in charge separation and transport and hence the hydrogen evolution activity of the photocatalyst. Herein, we have demonstrated the cocatalytic activities of two different metal-organic frameworks: CoFe-Prussian blue analog (CoFe-PBA) and CoFe-nitroprusside (CoFe-NP) loaded on CdS nanorods. The replacement of a -CN group of PBA with a strong π-acidic ligand, -NO, produces NP with a significant difference in the electronic structure. The introduction of -NO results in an increased positive charge density on the metal centers of CoFe-NP, making it more susceptible to charge carrier transport from CdS through strong back donation than CoFe-PBA. Under the best reaction conditions, NP-CdS-2 produces hydrogen at a rate of 1735 μmol g−1 h−1, significantly higher than those of bare CdS and PBA-CdS. Moreover, transient absorption spectroscopy has revealed a long-lived charge separated state in NP-CdS-2 to enhance the photocatalytic activity. © 2023 The Royal Society of Chemistry.